1973
DOI: 10.1073/pnas.70.3.649
|View full text |Cite
|
Sign up to set email alerts
|

A New Complement-Mediated Cytolytic Mechanism—the C1-Bypass Activation Pathway

Abstract: A new cytolytic pathway is described whereby cells sensitized with cytotoxic antibody can be specifically iysed in the complete absence of intact, classical complement pathway function. Evaluation of this model with sera deficient in the 4th (C4), 2nd (C2), and 6th (C6) components of complement has revealed that this new Iytic mechanism, termed the Cl-bypass activation pathway, is initiated by the antibody-mediated activation of C1. Utilizing components of the previously described alternate complement pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…However, it appears that opsonization can proceed via another heat-labile pathway when C2 is blocked but not wheni Cl is blocked. Other investigators (51,52) have demonstrated that C1 can play a role in the activation of the alternative complemiient pathway (the "Cl-bypass" mechanism). From the results in this study, it appears that the C l-bypass mav be operative in the opsonization of S. atureus H peptidoglycani by C2-deficient serum, and that blockiing Cl thereby interferes with alternative pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that opsonization can proceed via another heat-labile pathway when C2 is blocked but not wheni Cl is blocked. Other investigators (51,52) have demonstrated that C1 can play a role in the activation of the alternative complemiient pathway (the "Cl-bypass" mechanism). From the results in this study, it appears that the C l-bypass mav be operative in the opsonization of S. atureus H peptidoglycani by C2-deficient serum, and that blockiing Cl thereby interferes with alternative pathway activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neither mannoserich SH5770 nor mannose-free S. adelaide activated significant amounts of Cl s in the presence of MBP, Cl r, and C ls. We considered briefly the possibility that MBP may activate complement via the unconventional Cl-bypass pathway (41,42). However, MBP-mediated complement fixation occurred in the absence of calcium, and therefore Cl -bypass was not considered further.…”
Section: Introductionmentioning
confidence: 99%
“…Because of these contradictory results, we examined the possibility of participation of alternative pathway factors : 1) heat treatment of the partially purified C4 fraction from mouse EDTA-plasma showed no effect on C4 activity (50°C, 20 min), 2) C4 activity could not be measured in VBS containing 10 mM EGTA and 5 mM MgCl2, 3) zymosan treatment of mouse serum also showed no effect on C4 activity (17°C, 15 min). From these results, our assay method proved to be functional C4 titration and also ruled out the participation of the Cl-bypass pathway which was described by May and Frank (1973) as a mechanism for lysing sheep E heavily sensitized with rabbit antibody using C4 deficient guinea pig serum. Therefore, it will be difficult to consider that the Ss protein is a functional C4 molecule itself.…”
Section: Discussionmentioning
confidence: 84%